Family Firm Brands, Perceptions of Doing Good, and Consumer Happiness. (September 2019) - Schellong, Margarete; Kraiczy, Nils D.; Malär, Lucia; Hack, Andreas
This research examines how and why family firm brands (compared to nonfamily firm brands) affect consumers. We argue that a brand's family firm status acts as a signal to consumers who share category-based beliefs about family firms doing good due to preserving their socioemotional wealth. This perception in turn is a fair and positive appraisal in the mind of consumers (in the sense of indirectly benefiting others with their spent financial resources) that elicits happiness. In an experimental study, we show that family firms are being perceived by consumers as acting more supportive towards internal and external stakeholders and that these perceptions in turn result in higher consumer happiness. In other words, our results indicate that communicating a brand's family firm status might have a positive indirect influence on consumer happiness through the perception of doing good. On the other hand, our results suspect that a brand's family firm status might also trigger beliefs (not part of our study) with more negative indirect effects on consumer happiness.